Vesoljna Cerkev kot primer globaliziranega pravnega reda - Košir, Borut (Bogoslovni vestnik, 2003)
The Christian Chuch is the oldest globalized society of the modern world. The problems encountered by the modern process of connecting nations, states and different cultures were encountered by the Church at its beginnings. It solved them primarity by the contents of its mission of preaching the Gospel it had received from its founder. In this process it was able to aapreciate the different regional peculiarities entering the universal Church. Also with regard to the legal system, the Church is a sign of harmony between the universal regulations of its activity and the regional laws governing the activity of single local Churches. The article tries to show the good and the bad dimensions of globalization. After having explained the legal relation between the universal Church and the local Churches based on the quality of the contents, this pattern is presented as one of the possibilities to solve the numerous difficulties experienced by the modern society in globalization processes.
Keywords: capitalism; Catholic Church; evropska kultura; globalizacija; globalizacijski procesi; globalization; hierarhija; jezik; kapitalizem; katoliška cerkev; Language; narod; organska družba; people; pragmatizem; pravni red; šengenske meje; trade; trgovina; vrednote